Reading Predictors in Croatian : Contribution of (Meta)Phonological Variables = Prediktori čitanja u hrvatskome jeziku : doprinos (meta)fonoloških varijabli - Kelić, Maja (Array, 2021)
Phonological awareness (PA), rapid automatised naming (RAN) and working memory (WM) are considered to be the most important factors supporting reading development. However, their relative importance varies across orthographies and age. The goal of this study was to examine reading predictors in Croatian, a language with highly transparent orthography, after three years of formal reading instruction. The study included 80 participants (mean age: 10.07 years). Reading rate and accuracy were measured using lists of words and pseudowords, and PA was measured using phoneme deletion, phoneme addition and spoonerism tasks. RAN was measured using naming of colours, and WM was measured using the WM standardised measure of digit span (WISC-IV-HR) and pseudoword repetition. In order to find the best predictors of reading rate and accuracy for both words and pseudowords, three-stage hierarchical multiple regression was conducted. The results showed that in highly transparent language when reading is automatised, RAN is the most significant predictor of both reading rate and accuracy. Although this study did not show dissociation between the predictors supporting reading speed and reading accuracy, it confirmed the importance of PA as a suppressor variable for RAN in predicting pseudowords reading time.